Effect of Hormone Replacement Therapy on Bone Mineral Density and Body Composition in Chinese Adolescent and Young Adult Turner Syndrome Patients - Li, Li; Qiu, Xiu; Lash, Gendie E.; Yuan, Lianxiong; Liang, Zichao; Liu, Li (Frontiers in Endocrinology, 2019)
Low bone mineral density (BMD) is one of the major health problems in Turner syndrome (TS) patients, and a certain percentage of TS girls are treated with hormone replacement therapy (HRT) to improve their BMD, among other health benefits. While it is generally accepted that HRT improves BMD and body composition in adolescent and young adult TS patients, studies of HRT in Chinese TS patients are limited. Methods: To investigate the effects of HRT in Chinese TS girls, we performed a longitudinal observational study which compared measurement of BMD and body composition by dual energy X-ray absorptiometry (DXA) using a Lunar DXA densitometer in 20 Chinese adolescent and young adult TS patients (average age = 18) before and after 1 year of HRT treatment. Results: Whole body BMD (0.85g/cm2 vs 0.87 g/cm2, P<0.001), femur neck BMD (0.6 g/cm2 vs 0.62 g/cm2, P=0.02), total hip BMD (0.68 g/cm2 vs 0.71 g/cm2, P=0.003) and whole body lean mass (30.39 kg vs 31.66 kg, P=0.002) were significantly increased in these patients after 1 year HRT treatment, but there was no difference in whole body fat mass, android:gynoid ratio and lumbar spine BMD. Conclusions: In summary, our study found that HRT was an effective way to increase whole body BMD, femur neck BMD, total hip BMD and whole body lean mass in Chinese TS girls, with no effect on whole body fat mass, android:gynoid ratio or lumbar spine BMD.